2022
DOI: 10.3390/s22145319
|View full text |Cite
|
Sign up to set email alerts
|

Rivers’ Water Level Assessment Using UAV Photogrammetry and RANSAC Method and the Analysis of Sensitivity to Uncertainty Sources

Abstract: Water-level monitoring systems are fundamental for flood warnings, disaster risk assessment and the periodical analysis of the state of reservoirs. Many advantages can be obtained by performing such investigations without the need for field measurements. In this paper, a specific method for the evaluation of the water level was developed using photogrammetry that is derived from images that were recorded by unmanned aerial vehicles (UAVs). A dense point cloud was retrieved and the plane that better fits the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Besides its enhanced computational efficiency, RANSAC presents another important advantage in its scalability concerning the size of the input PC and the number and size of the shapes within the data. This algorithm has already been validated in other applications, such as the automatic extraction of building elements (e.g., roof planes and walls) [46,47], structural planes of rocky slopes [48], water-level planes [49], etc. In these studies, the application of RANSAC has demonstrated efficient performance, even in photogrammetric PCs, which are typically noisier than those obtained through TLS or LiDAR.…”
Section: The Ransac Approachmentioning
confidence: 99%
“…Besides its enhanced computational efficiency, RANSAC presents another important advantage in its scalability concerning the size of the input PC and the number and size of the shapes within the data. This algorithm has already been validated in other applications, such as the automatic extraction of building elements (e.g., roof planes and walls) [46,47], structural planes of rocky slopes [48], water-level planes [49], etc. In these studies, the application of RANSAC has demonstrated efficient performance, even in photogrammetric PCs, which are typically noisier than those obtained through TLS or LiDAR.…”
Section: The Ransac Approachmentioning
confidence: 99%
“…The circle fitting methods commonly used include mean method [17], RANSAC method [18], least squares method [19], etc. Since the mean and least squares methods are sensitive to interference points, the RANSAC algorithm has the strongest resistance to interference, so the RANSAC algorithm is chosen to obtain the fitted circle.…”
Section: Construction Of Characteristic Curvementioning
confidence: 99%
“…An example of simple shape detection in nature can be found in [ 91 ], where the authors develop a method for monitoring the water level in a river for a flood warning system. A UAV records aerial images, and a dense point cloud is obtained from them using photogrammetric software.…”
Section: Applicationsmentioning
confidence: 99%
“…Open3D is the library behind indoor3D, the library for processing 3D data from indoor scenes [ 109 ]. Another Python library not mentioned so far is pyRANSAC-3D [ 129 ], employed, for example, in [ 91 ]. The characteristics of these libraries, along with those previously presented, are summarized in Table 5 .…”
Section: Softwarementioning
confidence: 99%